2020
DOI: 10.1111/1556-4029.14323
|View full text |Cite
|
Sign up to set email alerts
|

Error Rates, Likelihood Ratios, and Jury Evaluation of Forensic Evidence

Abstract: Forensic examiners regularly testify in criminal cases, informing the jurors whether crime scene evidence likely came from a source. In this study, we examine the impact of providing jurors with testimony further qualified by error rates and likelihood ratios, for expert testimony concerning two forensic disciplines: commonly used fingerprint comparison evidence and a novel technique involving voice comparison. Our method involved surveying mock jurors in Amazon Mechanical Turk (N = 897 laypeople) using writte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…We did not ask judges about other interventions designed to educate jurors, which themselves might require judicial education. For example, jury instructions might convey additional information to jurors about the strength and limitations of forensic evidence (Garrett, Crozier, & Grady, 2020). Or judges may instead approve funding for a defense expert, who might call attention to limitations of the relevant discipline.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…We did not ask judges about other interventions designed to educate jurors, which themselves might require judicial education. For example, jury instructions might convey additional information to jurors about the strength and limitations of forensic evidence (Garrett, Crozier, & Grady, 2020). Or judges may instead approve funding for a defense expert, who might call attention to limitations of the relevant discipline.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…It is important to note that this technology is not based on phonetics as discussed in literature review section however; there is a wide range of experts who have shown doubts and concerns about the validity and reliability. There is also research presented by business experts who used simulation tools in lab settings and concluded that VRA can be used to detect proxies for deception (Garrett, Crozier, and Grady, 2020).…”
Section: Deception Detectionmentioning
confidence: 99%
“…Further, Mitchell and Garrett [3] found that laypeople assume fingerprint examiners are highly proficient, but it is possible that laypeople do not make this same assumption for other forensic disciplines, such that the effect of proficiency information may vary between forensic science disciplines and/or be amplified by effective cross-examination. Indeed, Garrett et al [15] provided laypeople with error-rate information regarding both fingerprint and voice comparison evidence, and they found that this information reduced guilty verdicts in the fingerprint condition, but it did not affect the weight given to voice comparison evidence, which was universally low. However, their study did not manipulate the individual examiner's error rate, but rather presented jurors with general error rates for each domain.…”
mentioning
confidence: 99%
“…Prior research has found that jurors tend to place strong weight on fingerprint evidence, regardless of how the examiner phrases ultimate conclusions [20]. However, jurors' beliefs about the reliability of other forms of forensic evidence appear to vary between disciplines [15,21,22]. Unlike fingerprint evidence, few studies have been done examining how jurors evaluate bitemark evidence.…”
mentioning
confidence: 99%